Urolithin B, a newly identified regulator of skeletal muscle mass. Issue 4 (1st March 2017) - Rodriguez, Julie; Pierre, Nicolas; Naslain, Damien; Bontemps, Françoise; Ferreira, Daneel; Priem, Fabian; Deldicque, Louise; Francaux, Marc
Abstract: Background: The control of muscle size is an essential feature of health. Indeed, skeletal muscle atrophy leads to reduced strength, poor quality of life, and metabolic disturbances. Consequently, strategies aiming to attenuate muscle wasting and to promote muscle growth during various (pathological) physiological states like sarcopenia, immobilization, malnutrition, or cachexia are needed to address this extensive health issue. In this study, we tested the effects of urolithin B, an ellagitannin‐derived metabolite, on skeletal muscle growth. Methods: C2C12 myotubes were treated with 15 μM of urolithin B for 24 h. For in vivo experiments, mice were implanted with mini‐osmotic pumps delivering continuously 10 μg/day of urolithin B during 28 days. Muscle atrophy was studied in mice with a sciatic nerve denervation receiving urolithin B by the same way. Results: Our experiments reveal that urolithin B enhances the growth and differentiation of C2C12 myotubes by increasing protein synthesis and repressing the ubiquitin–proteasome pathway. Genetic and pharmacological arguments support an implication of the androgen receptor. Signalling analyses suggest a crosstalk between the androgen receptor and the mTORC1 pathway, possibly via AMPK. In vivo experiments confirm that urolithin B induces muscle hypertrophy in mice and reduces muscle atrophy after the sciatic nerve section. Conclusions: This study highlights the potential usefulness of urolithin B for the treatment of muscle mass loss associated with various (pathological) physiological states.